Estudo comparativo entre osciladores para sensores indutivos de proximidade no projeto de circuitos integrados - Silva, Daniely Gomes (2013)
This work presents a study on proximity inductive sensors, in particular the eddy current types. Two types of circuits capable of detecting metal objects at large distances (12mm) will be discussed. The first one uses an operational amplifier oscillator with positive feedback. The second topology is based on a cross-coupled oscillator with negative transconductance. Both operate at a frequency of 257kHz. The second model has advantages such as greater simplicity for integration, small silicon area, reduced cost, low power consumption, and the possibility of achieving a satisfactory hysteresis adjustment for sensor operation. It was also verified its thermal drift for different sensing distances. This structure proved to be the best solution and was chosen to be implemented in a 0.6??m CMOS technology.